HUBUNGAN ANTARA TINGGI BADAN, BERAT BADAN, INDEKS MASSA TUBUH, DAN UMUR TERHADAP FREKUENSI DENYUT NADI ISTIRAHAT SISWA SMKN-5 DENPASAR - I Nengah Sandi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2013)
Has done research on students' Sekolah Menengah Kejuruan (SMK) Negeri-5 Denpasar. This research is connected between the body height (BH), body weight (BW), body mass index (BMI), and age on the resting pulse rate changes. The study was conducted in Cross Sectional Analytic in September 2011 on the class I and II SMK Negeri-5 Denpasar. The selection of a random sample of the group (cluster random sampling) with a simple random draw of the eight classes as a cluster to get the three classes. Of the three classes of 33 students chosen as men who do not have physical abnormalities and are willing as a research subject. Measurements for body height, body weight, body mass index, age, and the resting pulse rate was conducted in o'clock in the afternoon at 5:00 to 19:00 pm at GOR Ngurah Rai Denpasar. Data were analyzed by correlation of Pearson (Pearson Correlation) at the 0.05 significance level. From the analysis found no association between IMT with the resting pulse rate with r = 0.540 and p = 0.001, between the ages of the resting pulse rate with r = 0.460 and p = 0.007 (p ? 0.05) and there is no relationship between body weight and body height with the resting pulse rate with a value of r and p respectively, r = - 0.146 with p = 0.417 and r = 0.190 with p = 0.290 (p > 0.05). Thus, the resting pulse rate is directly influenced by age and BMI with positive correlation.